Refractory Infection of Mycobacterium abscessus: Skin and Soft Tissue Infection Recurred under Combination Therapy of Surgery and Outpatient Antibiotics - Atsuki Yamada; Ken Yukawa; Tomoaki Eguchi (Journal of Plastic and Reconstructive Surgery)
Mycobacterium abscessus (M. abscessus) is a nontuberculous mycobacterium that causes skin and soft tissue infections. Treatment methods for these infections, including the type and duration of antimicrobial agents, have not been established. The function of surgery is also unknown. We report a case of skin and soft tissue infection of the left upper arm in a healthy 47-year-old Japanese man who was treated with complete surgical excision and antimicrobial therapy as feasible on an outpatient basis, which resulted in relapse <1 month later. Given the possibility of developing antibiotic-resistant bacteria, insufficient antimicrobial treatment should not be administered without careful consideration. There are currently few effective oral antimicrobial agents against M. abscessus, so careful antimicrobial therapy along with hospitalization (at least during the early treatment phase) is preferred, regardless of the use/nonuse of surgical treatment.